Balancing performance-based expectations with a holistic perspective on coaching: a qualitative study of Swedish women's national football team coaches' practice experiences. (18th December 2017) - Lindgren, Eva-Carin; Barker-Ruchti, Natalie
ABSTRACT: Purpose : The purpose of this study was to explore how an exclusive sample of women's national football team coaches described how they implement careful coaching while facing social and organizational pressure to win medals.Method : To consider coaches' negotiations, we drew on Noddings' concept of caring. Using an interpretive research paradigm, we conducted in-depth interviews with five Swedish women's national football team coaches. An abductive approach was used to simultaneously process the theoretical framework of "ethics of care" and the empirical data.Results : The coaches unanimously adopted a holistic perspective to coaching. The coaching strategies they described included promoting players' development, well-being, and sustainable elite performance; listening to the players' voices and engaging in dialogue; and creating a positive environment and promoting fair play.Conclusions : These findings demonstrate that the women coaches, despite performance pressure, adopt caring coaching in the form of Noddings' pedagogical modelling, dialogue, and confirmation strategies, and provide an example of how coaches can adopt caring, holistic, and athlete-centred coaching while working at the highest level of competitive sport and achieving competitive success.